Introduction: Ethical issues in educational research. (January 2020) - Butterwick, Shauna; Head, George; Madalinska-Michalak, Joanna; Raykov, Milosh; Taylor, Alison; Taylor-Neu, Robin; Zgaga, Pavel
This special issue of the European Educational Research Journal (EERJ) addresses the issues surrounding current concerns regarding the ethical conduct of research in education. The impetus for ethical regulation of educational research has come from our institutions; therefore, by its very nature it is bureaucratic and often perceived by researchers as obstructive and even unethical. The papers herein tackle these problematic matters by interrogating the difficult questions surrounding ethical processes and charting academics' experiences of and reactions to them. The issue argues that academics need to take possession of this debate through practice so that it becomes an aid to research, enhancing the conduct of research and the dignity, privacy and humanity of researchers and their participants.